Marketing Communication For Colleges Through The Word-Of-Mouth Method - indra budaya; Gampo Haryono; Afdal Chatra Perdana; Dona Elvia Desi (International Journal of Artificial Intelligence Research, 2022)
Promotion of a university can be done using the Word-of-Mouth marketing communication method. This marketing method will use its consumers to promote its products to others. This promotion can be done using interpersonal communication. This study aims to find a model of word-of-mouth marketing communication that occurs at the STIE Sakti Alam Kerinci college. A qualitative approach through exploratory methods will be used in this study. This study then found that before deciding to go to college, the perpetrator of the communication would consider the situational and personal factors of the interlocutor. By using the communication model of Riley and Riley as its foundation, the word-of-mouth model is strongly influenced by the activities that occur between personal communication between its members.